Enstranglements: Performing Within, and Exiting From, the Arts-in-Health “Setting” - Williams, Frances; Shaw, Becky; Schrag, Anthony (Frontiers in Psychology, 2022)
Abstract The following text explores performative art works commissioned within a specific ‘arts and health’ cultural setting, namely that of a medical school within a British university. It examines the degree to which the professional autonomy of the artists (and curator) were 'instrumentalized' and diminished as a result of having to fit into normative frames set by institutional agendas (in this case, that of ‘the neoliberal university’). We ask, to what extent do such 'entanglements', feel more like ‘enstranglements’, suffocating the artist's capacity to envision the world afresh or any differently? What kinds of pressures allow for certain kinds of ‘evidence’ to be read and made visible, (and not others)? Are You Feeling Better? was a 2016 programme curated by Frances Williams, challenging simplistic expectations that the arts hold any automatic power of their own to make ‘things better’ in healthcare. It included two performative projects – The Secret Society of Imperfect Nurses, by Anthony Schrag with student nurses at Kings College London, and Hiding in Plain Sight by Becky Shaw (plus film with Rose Butler) with doctoral researchers in nursing and midwifery. These projects were situated in a climate of UK National Health Service cuts and austerity measures where the advancement of social prescribing looks dangerously like the government abnegating responsibility and offering art as amelioration. The text therefore examines the critical ‘stage’ on which these arts-health projects were performed and the extent to which critical reflection is welcomed within institutional contexts, how learning is framed, expressed aesthetically, as well as understood as art practice (as much as ‘education’ or ‘learning’). It further examines how artistic projects might offer sites of resistance, rejection and mechanisms of support against constricting institutional norms and practices that seek to instrumentalize artistic works to their own ends.